The Effectiveness of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in Patients With Undiagnosed Lung Cancer - Gül, Şule; Niksarlıoğlu, Elif Yelda; Yeter, Ayşe (Acta Medica, 2021)
Objectives: Conventional bronchoscopic techniques and computed tomography-guided transthoracic needle aspiration are widely used in the diagnosis of lung cancer. In some patients diagnosis can be challenging. Endobronchial ultrasound-guided transbronchial needle aspiration can be used in the diagnosis of lung cancer after procedures have failed to provide a diagnosis. We aimed to show the effectiveness of Endobronchial ultrasound-guided transbronchial needle aspiration in the diagnosis of lung cancer in view of the literature and to share the experience from Turkey. Material and Methods: This was a retrospective study conducted between 2014 and 2019. Forty-five patients who were suspected of having lung cancer and underwent Endobronchial ultrasound because diagnosis was not confirmed using methods such as bronchoscopy, computed tomography transthoracic needle aspiration, and peripheral lymph node excision, were included in the study. Results: Three hundred sixty-eight Endobronchial ultrasound procedures were performed. Forty-five patients met the inclusion criteria and were included in the study. Using Endobronchial ultrasound, samples were taken from only mass in eight patients (17.8%), lymph nodes in 30 patients (66.7%), and mass + lymph node in seven (15.5%) patients. Minor complications were seen in five (11.1%) patients and no major complications were seen. Definitive diagnosis was obtained in 35 (77.7%) patients with Endobronchial ultrasound guided transbronchial needle aspiration. Non-small cell lung cancer was identified in 16 patients (45.7%), small cell lung cancer was seen in 15 (42.8%) patients. Seven of ten undiagnosed patients underwent surgical procedures. Conclusion: Endobronchial ultrasound, is an effective and safe method for diagnosing lung cancer after undiagnosed procedures. In selected cases, it can be the first choice for the diagnosis of lung cancer.